Knowledge Management - A Learning And Growth Perspective Of Balance Score Technique With Reference To Tidc In Chennai City - DR. R.POORNIMARANI,, Ms. K.KARPAGAMBIGAI, (Design Engineering, 2021)
Knowledge Management (KM) is a deliberate, systematic business optimization strategy that selects, distills, stores, organizes, packages and communicates information essential to the business of a company in a manner that improves employee performance and corporate competitiveness. Knowledge management is the key to the effective management of the company. From the business perspective, Knowledge Management is useful only if information is used in a directed manner, such as to improve employee performance. If the information is useful, it should directly impact employee behavior and be reflected in increased efficiency, effectiveness, or diligence.